2012
DOI: 10.1177/1479164112456310
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the histomorphology and molecular biology of radial artery conduits in patients with diabetes mellitus who underwent coronary bypass surgery

Abstract: We studied the impact of diabetes mellitus (DM) on the radial artery (RA) in 30 patients with DM and 30 non-diabetic patients undergoing coronary artery bypass grafting with autologous RA. RAs were recorded as normal if there was no cellular or stromal tissue between the endothelium and the internal elastic lamina. The RA was normal in 26.7% of diabetic and 76.7% of non-diabetic patients (p = 0.000298). Intimal thickness index and intima:media ratio were higher in the former than in the latter (p < 0.05; p < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Shah et al reported that each 1% increase in HbA1c or each year of duration of diabetes is associated with approximately 30% increased odds of a thicker carotid intima media thickness. Zou et al found that intimal thickness and intima media ratio are increased in diabetic patient's radial artery grafts in comparison with non diabetics using electron microscopy. Chowdury et al also found increased medial calcification and atherosclerosis of the radial artery grafts in diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…Shah et al reported that each 1% increase in HbA1c or each year of duration of diabetes is associated with approximately 30% increased odds of a thicker carotid intima media thickness. Zou et al found that intimal thickness and intima media ratio are increased in diabetic patient's radial artery grafts in comparison with non diabetics using electron microscopy. Chowdury et al also found increased medial calcification and atherosclerosis of the radial artery grafts in diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…Due to easy accessibility and low rate of associated complications, the radial artery is favored in various clinical procedures, such as for a bypass conduit during coronary artery bypass graft (CABG) surgery, 12 , 13 as the site of cardiac catheterization in coronary angiography, 14 and as the route of cannulation for continuous monitoring of arterial pressure. 2 In addition, the artery's vascular response to external stimuli (vasoreactivity) has been investigated extensively.…”
Section: Discussionmentioning
confidence: 99%
“… 2 In addition, the artery's vascular response to external stimuli (vasoreactivity) has been investigated extensively. 13 , 15 - 17 Radial artery harvest has shown mild reduction in digital perfusion and complementary increase in ulnar artery diameter and flow velocity with no clinical sequelae or compromised hand function. 18 , 19 After catheterization for coronary angiography access, the artery may exhibit reduced lumen density due to wall injuries after cannulation.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have established the association of diabetes with impaired endothelial function and decreased NO bioavailability in RA grafts. Atherosclerotic process in diabetic patients was morphologically and functionally shown to be ahead of non-diabetic RA (28, 29). Optical coherence tomographic imaging of otherwise ‘normal’ RA revealed plaques in 76% of diabetic patients undergoing CABG surgery (30).…”
Section: Discussionmentioning
confidence: 99%